Morality, perceived risk and product attributes as determinants of intent to purchase pirated VCD/DVD - Del Rosario, Michael E. (Animo Repository, 2005)
This paper examines the effect of morality, perceived risks, product attributes and demographic variables on the intention to purchase pirated VCD/DVD. Primary data was gathered in major Metro Manila shopping malls using systematic sampling. Descriptive statistics, hierarchical regression and stepwise regression were used in this study. Findings indicated that in the moral intensity factors, probability of effect to producers has a positive influence on purchase intent. Consumers think that when they contribute more to the losses of producers, the more likely they will intend to purchase pirated VCD/DVD. However, temporal immediacy to producers and social consensus from relative posted a negative significance. Performance, financial and prosecution risks were not felt by the consumers in making a pirated purchase decision. Only social risk from friends and relatives were seen to have an effect on intention to buy pirated CDs. In terms of product attributes, quality, durability and accessibility were found to have a positive influence. The more consumers think that pirated VCD/DVD will last for more than a year, will have a clear sound and picture and can be bought at convenient locations, the more likely they will buy. Results also showed that consumers may think buying pirated products is wrong when taking note of the possible risk and moral intensity of their actions. However, when taking into consideration product attributes, results were different. It was evident that consumers do not consider the moral aspect involved in the act. Among the demographic variables, income and educational attainment were found to be significant. The positive effect on purchase intent explains that individuals with higher income and higher levels of education have a greater likelihood to make pirated purchase. Findings also revealed that those respondents with previous purchase experience tend to be more likely to buy such products. It is hoped that these findings will help the Optical Media Board and producers/manufacturers of original CDs in policy and marketing strategy formulation.